Role of Melatonin in the Onset of Metabolic Syndrome in Men - Elham Hasan Mahmood; Nihad Nejres Hilal (University of Mosul, 2024)
Background:  This prospective hospital-based study conducted in Tikrit City (Iraq) aimed to investigate the role of melatonin and the level of haemoglobin A1c and lipid profile concentrations in metabolic syndrome patients. The present study sought to identify the role of serum melatonin in MetS male patients. Methods: Participants were all males aged 18-50 years. A total of 60 metabolic syndrome male patients versus 30 healthy control male participants were enrolled in the present study. Blood samples were collected at a specific time (10 P.M. to 1 A.M.) and analyzed for measurement of haemoglobin A1c, lipid profile and melatonin. Results: Melatonin is significantly (p>0.001) lower in patients with metabolic syndrome (206.55 ±105 pg/ml) compared with the control group (298.82±110.4 pg/ml).  The metabolic syndrome has significantly (p >0.001) elevated HbA1c % and lipid profile compared with the control group. Conclusion: In metabolic syndrome patients, serum melatonin concentration is reduced alongside elevated lipid profile glycemic control compared to normal people, these characteristics could participate in further enhancing the underlying pathology of metabolic syndrome diseases.